The Welfare State in Latin America: reform, innovation and fatigue - Sonia Fleury
Abstract: This paper analyses the challenges of building the Welfare State in late democracies in Latin America. The author shows how the literature has identified different social protection patterns in the region and how recent reform models have transformed institutions, in an unfavorable socioeconomic context. The results point to the emergence of a mixture of social protection measures that have increased coverage and reduced poverty, but are unable to guarantee universal citizens' rights and longevity.